DISRUPTIVE INNOVATIONS AND PERSONAL DATA PROTECTION: NEW CHALLENGES FOR THE LAW - de Araujo, Valter Shuenquener; Couto dos Santos Bilcherg Calil, Daniel (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2025)
ABSTRACT: Disruptive technological innovations interfere in the regulatory framework of public services and in the execution of economic activities. Therefore, they demand a new regulatory conformation that is able to absorb new demands and to allow competition between economic agents. In this context, the protection of personal data has evolved significantly nationally and internationally, which is why this subject should be deeply researched. The research is qualitative, bibliographic and descriptive of jurisprudence, doctrine and of the positive law.